Dissemination of Evidence-Based Practices for Anxiety Disorders in Wyoming: A Survey of Practicing Psychotherapists. (March 2013) - Hipol, Leilani J.; Deacon, Brett J.
Despite the well-established effectiveness of exposure-based cognitive-behavioral therapy (CBT) in the treatment of anxiety disorders, therapists have been slow to adopt CBT into their clinical practice. The present study was conducted to examine the utilization of psychotherapy techniques for anxiety disorders among community practitioners in a rural setting in order to determine the current status of the dissemination of CBT. A sample of 51 licensed psychotherapists from various mental health professions was recruited from online practice listings in the state of Wyoming. Participants completed a survey assessing their use of various psychotherapy techniques in the past 12 months for clients with obsessive-compulsive disorder, post-traumatic stress disorder, panic disorder, and social phobia. Nearly all psychotherapists reported providing CBT, and techniques such as cognitive restructuring, arousal-reduction strategies, and mindfulness were used by the vast majority of respondents. Therapist-assisted exposure was rarely utilized, and providers who delivered exposure therapy often did so alongside other techniques of questionable compatibility with this approach. Non-evidence-based techniques were frequently used, particularly by self-proclaimed anxiety specialists. Our findings highlight the successes and failures of efforts to disseminate exposure-based CBT to community practitioners. Implications for clinical training and practice are discussed.